2022
DOI: 10.1021/acsestwater.1c00441
|View full text |Cite
|
Sign up to set email alerts
|

Operational Constraints of Detecting SARS-CoV-2 on Passive Samplers using Electronegative Filters: A Kinetic and Equilibrium Analysis

Abstract: In developing an effective monitoring program for the wastewater surveillance of SARS-CoV-2 ribonucleic acid (RNA), the importance of sampling methodology is paramount. Passive sampling has been shown to be an effective tool to detect SARS-CoV-2 RNA in wastewater. However, the adsorption characteristics of SARS-CoV-2 RNA on passive sampling material are not well-understood, which further obscures the relationship between wastewater surveillance and community infection. In this work, adsorption kinetics and equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Researchers have also examined the equilibrium and kinetic adsorption of SARS-CoV-2 RNA onto passive samplers designed for wastewater surveillance. 21 In our review of the previous work described above, we noted the lack of laboratory partitioning and/or distribution data on key respiratory viruses in wastewater, including SARS-CoV-2, RV, and RSV, which have been shown to be present in wastewater matrices and correlate to community disease occurrence. 22,23 In addition, we noted that the experiments typically did not include temperature as an experimental factor and that laboratory and field experiments were rarely coupled.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have also examined the equilibrium and kinetic adsorption of SARS-CoV-2 RNA onto passive samplers designed for wastewater surveillance. 21 In our review of the previous work described above, we noted the lack of laboratory partitioning and/or distribution data on key respiratory viruses in wastewater, including SARS-CoV-2, RV, and RSV, which have been shown to be present in wastewater matrices and correlate to community disease occurrence. 22,23 In addition, we noted that the experiments typically did not include temperature as an experimental factor and that laboratory and field experiments were rarely coupled.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Partition coefficients (reported as K p in the paper) were 3.7 × 10 4 and 4.0 × 10 4 mL·g –1 in primary and secondary sludge, respectively. Researchers have also examined the equilibrium and kinetic adsorption of SARS-CoV-2 RNA onto passive samplers designed for wastewater surveillance …”
Section: Introductionmentioning
confidence: 99%
“…Various research teams have led efforts to develop passive sampling techniques, such as the Moore swab, for economical sampling of wastewater with superior performance to grab sampling. 71 73 In addition, researchers have also initiated efforts to develop molecular testing techniques that do not require expensive quantitative polymerase chain reaction (qPCR) equipment, such as loop-mediated isothermal amplification, 74 and have coupled these with passive samplers and electronegative membranes to allow rapid wastewater testing. 37 , 75 Researchers have also proposed paper-based testing devices and biosensors as future analytical platforms for near real-time surveillance of infectious agents in wastewater, although as of yet no proof of concept has been published.…”
Section: Discussionmentioning
confidence: 99%
“…5,7,19,47 High levels of suspended solids in wastewater may affect the adsorption of viruses to the electronegative membranes. Hayes and coworkers 49 demonstrated that adsorption of the virus to the sampling material is highly dependent of the characteristics of the water. Retention of solids can improve RNA recovery but and excessive retention can inhibit de RNA extraction process.…”
Section: Detection Of Human Viruses At a Wwtp And A Nh By Applying Tw...mentioning
confidence: 99%